Pendampingan Pastoral Konseling Bagi Istri yang Suaminya Terkriminalisasi - Sumeleh, Meidy (PT. Giat Konseling Nusantara, 2025)
This study discusses the importance of the wife's role in the family, the challenges faced in family life, the impact of criminalization, and the role of pastoral counseling. Marriage is designed by God for human happiness, with the wife playing a vital role in supporting the husband and creating a harmonious family. Challenges in family life can arise from both internal and external factors, including issues of criminalization, which can cause emotional and social trauma for the wife. Criminalization, the process by which an act is deemed illegal, can lead to instability within the family, role changes, and negative impacts on children. In situations where a husband is accused of child abuse, the wife often faces social stigma, identity crisis, and emotional trauma. Pastoral counseling plays a crucial role in providing spiritual and emotional support, helping individuals manage trauma, build resilience, and find new meaning in life. This support includes emotional support, mental health education, integration of theological and psychological principles, preventive functions, and building supportive communities. This qualitative research uses a pastoral case study approach (MSKP) to understand the holistic impact of criminalization on wives and the effectiveness of the legal system in handling such cases. The aim is to analyze the holistic impact on wives of criminalized husbands and examine the effectiveness of legal protection for criminalized individuals and their families.